Ultrastructure of the antennal sensilla of Alabama argillacea (Hübner, 1823) (Lepidoptera: Erebidae) - Andrezo Adenilton Santos; Valéria Wanderley-Teixeira; Glaucilane dos Santos Cruz; Daniela Maria do Amaral Ferraz Navarro; Luiz Carlos Alves; Fábio André Brayner; Álvaro Aguiar Coelho Teixeira (Revista Brasileira de Entomologia, 2019)
Insects have several types of sensilla, the characterization of which has been fundamental to understanding the mechanisms of sensory perception in different species. This study aimed to describe the ultrastructure of the sensilla present on the antennae of Alabama argillacea (Hübner, 1823) (Lepidoptera: Erebidae), an important pest of cotton (Gossypium hirsutum L.) crops, as well as their possible variation between sexes. To do this, the antennae of males and females of A. argillacea were analyzed using scanning electron microscopy. Sensilla morphometry was assessed using photomicrographs, from which the lengths and basal and apical diameters of sensilla were measured using the ImageJ program. Seven types of sensilla were identified on the antennae of A. argillacea: sensilla trichodea, sensilla chaetica, sensilla auricillica, sensilla coeloconica, sensilla styloconica, sensilla basiconica, and sensilla Böhm bristles. Differences between the sensilla of males and females were found in their lengths and basal diameters in the distal and proximal regions. This suggests that sensilla functionality may not only vary from one species to another, but also between sexes within the same species. Thus, further transmission electron microscopy and single sensillum recording studies may provide more detailed information on the sensilla of A. argillacea and their functions. Keywords: Antenna, Cotton leafworm, Morphometry, Scanning electron microscopy